2002
DOI: 10.3171/spi.2002.96.3.0273
|View full text |Cite
|
Sign up to set email alerts
|

Anterior cervical fusion with carbon fiber cage containing coralline hydroxyapatite: preliminary observations in 45 consecutive cases of soft-disc herniation

Abstract: Object. The purposes of bone substitutes for anterior cervical fusion (ACF) are immediate biomechanical support and osteointegration of the graft. The authors report their preliminary results in performing ACF in which carbon fiber cages (CFCs) containing coralline hydroxyapatite (HA) are used as bone substitute. Methods. During a 24-month period, anterior microsurgical discectomy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 21 publications
1
45
0
Order By: Relevance
“…The advantage would be that they could provide immediate stability and share the load on bone substitutes to prevent collapse. The results were comparable with those reported by some authors [1,6,16] who used other calcium phosphate ceramics. Additionally, the ample blood supply might be another reason for successful interbody fusion.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The advantage would be that they could provide immediate stability and share the load on bone substitutes to prevent collapse. The results were comparable with those reported by some authors [1,6,16] who used other calcium phosphate ceramics. Additionally, the ample blood supply might be another reason for successful interbody fusion.…”
Section: Discussionsupporting
confidence: 82%
“…Interbody fusion cages have been developed to avoid the complications related to bone harvesting from the donor site while increasing immediate stability of the cervical spine after decompression and promoting bony fusion [3,12,17] Some authors [1,6] recommended the use of anterior cervical fusion with cage containing bone substitutes. Satisfactory results were obtained regarding the fusion rates although fusion was delayed as compared with that in a cage containing autograft [6].…”
Section: Introductionmentioning
confidence: 99%
“…Agrillo et al [1] implanted 57 cages packed with coralline hydroxyapatite and reported no implant-related complications and complete fusion in all patients at 12 months. Tancredi et al [25] also reported 119 carbon fiber cages packed with autograft, allograft or hydroxyapatite.…”
Section: Radiographic Evaluationmentioning
confidence: 97%
“…Several studies have investigated the feasibility of using carbon fiber cages in the cervical spine with autograft, allograft and hydroxyapatite graft material [1,18,19,25]. Few randomized studies that compare carbon fiber cages with a standard procedure exist [22].…”
mentioning
confidence: 99%
“…Following the long-lasting use of autografts and allografts [2,7,8,12,15,24,36,39], intervertebral cages, without or with additional anterior cervical plates, became the most commonly used intervertebral devices [1,14,25,27,30,39].…”
Section: Introductionmentioning
confidence: 99%